Finite-precision stabilization for neutrosophic linear systems using a descriptor model approach - Rongyao Ling; Songquan Shi; Wenhua Cui; Yiming Fang (Neutrosophic Sets and Systems)
This paper focuses on the stabilization problem of neutrosophic linear systems using finite-precision digital controllers. The main challenge lies in decoupling and processing the indeterminacies inherent in such systems. To tackle this, a standardization method that unifies the bounds of parameter indeterminacies is first proposed. Additionally, a fixed-point representation scheme is introduced to define both the precision and representation of the controller parameters. To handle multiple uncertainties in the system, a descriptor model approach is introduced, which transforms the closed-loop system into a singular system, allowing for more effective decoupling of uncertainties. Using singular system theory, a novel solvability condition is derived for system stabilization and a parametric approach for controller design is introduced, accompanied by a numerical example to validate the proposed methods.